Penerapan Hypnobrithing terhadap Penurunan Kecemasan pada Ibu Post Partum Spontan di RS Permata Medika Semarang - Firman Maulana; Yuni Endrawati; Mega Indah; Rika Nur’aini; Mustaniroh Mustaniroh; Wahyuningsih Wahyuningsih (Jurnal Siti Rufaidah, 2026)
The postpartum period is a phase of physical and psychological adaptation that often causes anxiety in mothers after childbirth. Untreated anxiety can affect the recovery process, breast milk production, and mother–infant bonding. This study aimed to determine the effectiveness of hypnobirthing in reducing anxiety levels among mothers with spontaneous postpartum. The method used was a case study with a nursing care approach involving five spontaneous postpartum mothers who experienced anxiety related to situational crises. Anxiety levels were measured using the Hospital Anxiety and Depression Scale (HADS) questionnaire before and after the intervention. The nursing intervention in the form of hypnobirthing was administered once daily for 15 minutes over three consecutive days. The results showed a decrease in the average anxiety score from 18 (severe anxiety) before the intervention to 10 (mild anxiety) after three days of hypnobirthing. All patients experienced a reduction in anxiety levels, with most achieving a final category of mild anxiety. In conclusion, hypnobirthing is effective in reducing anxiety levels in spontaneous postpartum mothers and can be used as a non-pharmacological nursing intervention to support maternal psychological recovery after childbirth.